TELAAH METODOLOGI ILMU ALQURAN: Konstruksi, Dekonstruksi, dan Rekonstruksi Ilmu Makkiyyah-Madaniyyah - Munawir Munawir (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2020)
Makkiyah-Madaniyyah as a science, in its development must having a shift in paradigma (shifting paradigm). From the old construction as an established  science (normal science), then experiencing anomalies and crises, and finally rise to a new paradigm.  The paradigm shif in a scientific building is something that is inevitable. This is not because the old scientific building is wrong, but because the old scientific is less supported to solve the current problems, till a new scientific building is needed. This article examines the process of developing the Makkiyah-Madaniyyah science. Through a descriptive  study of the construction of old Makkiyah-Madaniyyah science, then analyzed using the paradigm shift theory, then the answer was found that the reconstruction of the new Makkiyah-Madaniyyah was based on historical data especially the Prophet’s  migration from Makkah to Madinah, which then used historical data as a basis analysis reconstruct the values of usul (Universality) of the Qur’an and the values of furu’ (location and temporality) of Qur’an.